(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aimed to recognize the availability of Divergent and Convergent thinking skills in the content of the sixth scientific-grade mathematics bookfor the academic year 2020-2021by answering the key question of the research: What arethe divergent and convergent thinking skillsincluded in the sixth scientific-grade mathematics book? The researcher used the descriptive-analytical approach, to meet the objective of the research, . He develop a list of the divergent and convergent thinking skills and their sub-skills. Then, and after analyzing the content of the book,he checked the reliability of the analysisin two ways; the first is performed through analysis across time,and the reliability coefficient in this way reached 96%, the second is the reliability over the individuals, as the reliability coefficient in this way reached 94%, and that by using Holsti equation. The researcher has found that the divergent and convergent thinking skills included in the book disproportionately, as the deduction skill got the highest percentageof the divergent and convergent thinking skillsoverall, as it was (50%), the second was the interpretation skillby (16%), the third was the induction skillby (11%), while the fluency skill was the fourth one by (6%), the flexibility and classification skill came in the fifth by (5%), the sixth was for the originality skill by (3%), the seventh for the elaboration and comparison skill by (2%), and the last was for problem sensitivity by (0%), and according to this results, the researcher provided some recommendations, including reconsidering the content of the sixth scientific-grade mathematics book so that including the divergent and convergent thinking skills in balance, as well as making an experimental study to pursue the divergent and convergent thinking skills development among the students of sixth scientific-grade.